Neural Pragmatics in the Context of relevance Theory - Awat Ahmad Muhamadsalh Salih; Abdulwahid Musher Mahmood Dizaye (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The title of the research is Neural Pragmatics in the Context of relevance Theory. Pragmatics is the study of the neural principles of pragmatics, that is, the neural principles of the mental processes that produce communication to exchange delivery. The research should analyze neural pragmatics within the framework of communication and adaptation theory and give necessary examples in Kurdish language. The importance of this discussion is that it explains the mental processes in the mind, how meaning is perceived in the environment, and tries to develop specific protocols that reflect the daily communication situation to improve communication within the framework of the neuropragmatic project. The ultimate goal in neural pragmatics is to describe the neural construct and function of pragmatics as the system supports the full range of appropriate delivery behavior in surroundings and use. In this discussion, it is assumed that communication theory works within the framework of neuropragmatics. How does communication theory interpret the process of understanding? The discussion works within the descriptive approach and relies on the model. The content of the paper consists of two parts: the first part deals with neural pragmatics and its history and development, the second part deals with the theory of communication and mental representation of mental processes, with a summary in Arabic and English.